The history and development of the institute of Southeast Asia studies library, 1967-2012: Future issues and challenges - Lim, P.H. (2014)
The history and development of the Institute of Southeast Asian Studies (lSEAS) Library in Singapore can be seen in the annual reports of the Institute from 1970 to 2012. The researcher also visited the library about 20 times over a two-year period and referred to secondary information like journal articles to study the Library. The first phase of the Library covers the years 1969 to 1987 when the founder Librarian and her team developed the Library under the first four Directors of the Institute. This study looks at the issues and challenges relating to acquisition and collection development of the Library's materials. The second phase of the Library is the period when the second chief librarian succeeded the founder librarian from the years 1988 to 2012. The second phase marks the beginning of the introduction of Information and Communication Technology (lCT) in the Library, including multi-media materials. Finally, this study tries to identify the future policies and practices of the Library in areas of management, collection development and the provision of services for the different types of users. This study suggests that the ISEAS Library has developed to be a special for Southeast Asian Studies in Singapore when it contributed 65 per cent of original cataloguing records of its unique materials in the Singapore Integrated Library Automation System (SILAS) database in 1996. Recommendations were made to the like issues and challenges the Library will face in the future.